2004
DOI: 10.1158/0008-5472.can-04-1182
|View full text |Cite
|
Sign up to set email alerts
|

Limited Capability of Regional Lymph Nodes to Eradicate Metastatic Cancer Cells

Abstract: The capacity of lymph nodes to eradicate cancer is a controversial issue. The purpose of this study was to determine the interplay between tumor growth and host resistance at early stages of lymph node metastasis. A metastasis model was made in the rat mesenteric lymph node, and migration of cancer cells was visualized in vivo. The lymph node was removed for histologic analysis and cytokine measurement. Migrant cancer cells were initially arrested in the marginal sinus. After an initial increase, the number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 35 publications
1
27
0
2
Order By: Relevance
“…Lymphangiogenesis in regional lymph nodes plays an early role in spreading tumor cells though the lymphatic system to distant organs in gastric cancer. Nagata et al observed morphological changes in lymph nodes during the establishment of lymph node metastasis using a rat mesenteric SN model [26]. Watanabe et al reported that intranodal lymphatic vessel density was significantly correlated with the size of the metastasis [27].…”
Section: Discussionmentioning
confidence: 99%
“…Lymphangiogenesis in regional lymph nodes plays an early role in spreading tumor cells though the lymphatic system to distant organs in gastric cancer. Nagata et al observed morphological changes in lymph nodes during the establishment of lymph node metastasis using a rat mesenteric SN model [26]. Watanabe et al reported that intranodal lymphatic vessel density was significantly correlated with the size of the metastasis [27].…”
Section: Discussionmentioning
confidence: 99%
“…Sinus macrophages mediate the phagocytosis of cancer cells attached to the sinus wall and destroy them in order to inhibit their metastasis [26,27] . Sinus macrophages are also a part of an anti-cancer cytokine network involving TNF-␣ and IL-1 ␤ [28,29] . The genes expressed in the sinus macrophages in the lymph nodes and liver were distinct from those expressed in the splenic sinus macrophages, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Nagata et al (2004) [7] showed that macrophages beneath the marginal sinus form the first line of defense against cancer cell invasion. They also demonstrated that a variety of cytokines is secreted in the LNs of tumor-bearing animals and described that it is possible to modify the metastatic process by the artificial manipulation of the cytokine environment.…”
mentioning
confidence: 99%